Analysis of Legal Benefits in Handling Corruption and Capital Market Cases of PT. ASABRI - Jatna, R. Narendra; Ebenezer, Timotius Benjamin (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
This study aims to analyze the legal limitations in handling the PT ASABRI case which has the dimensions of corruption and capital market crimes. The focus of this study is that the prosecutor's office as investigator and public prosecutor in prosecuting the PT ASABRI case is required to make a choice in prosecuting the PT ASABRI case, namely choosing between the mechanism of corruption or capital market crimes. The prosecutor's office is faced with this choice because the PT ASABRI case which caused such fantastic state financial losses was carried out by carrying out a series of actions involving price manipulation on the capital market exchange. The research method used is the doctrinal research method with a prescriptive typology. The data collection technique used in this study is derived from legal prescriptions written in the law book or from documents such as regulations, articles concerning corruption and capital market crimes. Meanwhile, the data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of the study show that the selection of the use of the corruption crime mechanism by the prosecutor's office in handling the PT ASABRI case was appropriate, because it was in accordance with the principle of benefit and the principle of systematiche specialiteit in procedural law.